Konsep Hidden Layer pada Perancangan Taman Brumbungan Kota Semarang - Farida, Ariesa; Handoyo, Andreas; Purnomo, Agus Dody (Jurnal Arsitektur Lansekap, 2022)
Hidden layers concept in the design of the Semarang City Brumbungan Park. Brumbungan Park is an open space located on Jalan Pringgading, Central Semarang District, Semarang City. The Location of Brumbungan Park in the previous condition was a vehicle parking area for culinary stalls in the vicinity. In 2016 there was a discourse to restore this park according to its function as a city park and green open space. The Central Java Environmental and Building Arrangement Work Unit in collaboration with the Central Java Regional Indonesian Architects Association held a green open space design competition to produce designs that could be implemented in the park. The Brumbungan park design that is offered tries to answer the problems and issues that occur around the park, as well as being able to accommodate various functions and activities in the park. The methodology used in this study are qualitative method by data inventory, analysis and synthesis then design concept determination and development. The result of the planning is the Hidden Layer of Semarang design concept, which means that even on a small scale, this new garden design is expected to contribute to green open spaces in Semarang, set a precedent, open new discourses, and become a catalyst for the development of parks and open spaces. Physical implementation of the concept, this park will be hidden and surrounded by vegetation (hidden layer) so that the facilities will be enjoyed while in the park.